The Effects of High-fat Diet on Histological Changes of Kidneys in Rats - Hotimah Masdan Salim; Lintan Farizqi Kurnia; Tri Wahyu Bintarti; Handayani Handayani (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction Hypercholesterolemia contributes as a risk factor for endothelial dysfunction in the kidneys and worsens the condition of patients with previous kidney damage. This study aimed to examine the effect of hypercholesterol diet in kidney structure.Methods: This was an experimental study, a case control using eight-week-old Rattus novergicus, divided into control and treatment group. High-fat diet (HFD) was administrated orally to treatment group for 14 days. All data statistically analyzed with two-paired ANOVA and post hoc for comparison.Results: Histological analysis using hematoxylin-eosin staining showed degeneration in nephrons, including glomerulosclerosis, segmental necrosis and tubular defects. The mononuclear cell infiltration was Increased in HFD group significantly (P<0.05).Conclusion: We concluded that a high fat diet induced obesity and may lead to renal deformities as a result of histopathological changes such as dilatation, tubular defects, inflammation and connective tissue enlargement of the kidney.